Partial masculinization of Aedes aegypti females by conditional expression of Nix. - Bianca B Kojin; Emma Jakes; James K Biedler; Zhijian Tu; Zach N Adelman (Public Library of Science (PLoS), 2022)
Background Aedes aegypti, the main vector of dengue, yellow fever, and other arboviruses thrives in tropical and subtropical areas around the globe putting half of the world's population at risk. Despite aggressive efforts to control the transmission of those viruses, an unacceptable number of cases occur every year, emphasizing the need to develop new control strategies. Proposals for vector control focused on population suppression could offer a feasible alternative method to reduce disease transmission. The induction of extreme male-biased sex ratios has been hypothesized to be able to suppress or collapse a population, with previous experiments showing that stable expression of the male determining factor Nix in A. aegypti is sufficient to convert females into fertile males. Methodology/principal findings Here, we report on the conditional expression of Nix in transgenic A. aegypti under the control of the tetracycline-dependent (Tet-off) system, with the goal of establishing repressible sex distortion. A masculinization phenotype was observed in three of the seven transgenic lines with females exhibiting male-like long maxillary palps and most importantly, the masculinized females were unable to blood feed. Doxycycline treatment of the transgenic lines only partially restored the normal phenotype from the masculinized transgenic lines, while RT-qPCR analysis of early embryos or adults showed no correlation between the level of masculinization and ectopic Nix expression. Conclusions/significance While the conditional expression of Nix produced intersex phenotypes, the level of expression was insufficient to program full conversion. Modifications that increase both the level of activation (no tet) and the level of repression (with tet) will be necessary, as such this study represents one step forward in the development of genetic strategies to control vector-borne diseases via sex ratio distortion.